Transnational marriages in the North: Legal issues of Russian women married to Norwegian men - Brækhus, Hege (Umeå University, 2017)
Source at https://journals.ub.umu.se/njolas/article/view/24 This article is about the legal situation for the many women who immigrated to the northernmost county in Norway, Finnmark, from North-West of Russia after the fall of the Iron Curtain. Their way of immigration was mostly through marriage to Norwegian men. To be foreign and new in a country could be difficult. How is their legal situation as newcomers? The complexity of problems will increase if they get children, divorce or move from Norway to Russia or the other way. Which authorities are to decide for them and which country’s laws are to be applied? The article also covers the legal situation for children born in such marriages such as status, custody, support and child abduction, and the situation when one of the spouses dies.